The College Students’ Oral English Education Strategy Using Human-Computer Interaction Simulation System From the Perspective of Educational Psychology - Zhou, Ping; Wu, Xiaoliang; Xu, Hui; Wang, Guan (Frontiers in Psychology, 2021)
The role of human-computer interaction (HCI) system in college students' oral English learning is simply discussed to analyze the current situation of college students' oral English based on HCI simulation system. The purpose is to study the oral education of college students. First, the theories of educational psychology, HCI system and the current situation of college students' oral English learning are elaborated. Meanwhile, in oral English teaching, teachers use SVM (support vector machines) and multimodal fusion intention perception method in set theory to realize the interactive teaching between students and machines; then, the HCI simulation of oral English is explained. The current situation of college students' oral English learning is analyzed by questionnaire from the perspective of educational psychology. Finally, the HCI system in college students' oral English learning is explored based on the learning level detection. The results show that 12% of college students are unqualified in oral English; 25% of them think their oral English level is medium; most of college students' English learning anxiety is English progress anxiety; 18% of the students believe that they will study oral English for life; 32% of the students think that they have more opportunities to learn English at ordinary times, and most of the students learn English through English movies and songs after class. What attracts college students to learn oral English through HCI system is that learning is not limited by time and space. Most students hold that their English level is good, and hope that learning anxiety can be reduced through HCI system. The strategies of college students' oral English education with HCI simulation system is evaluated based on the perspective of educational psychology, providing a research basis for oral English education in other regions and even the whole country, so as to facilitate the better development of oral English education.